EDUCATION FOR ALL: READING ARTICLE 21A AND ARTICLE 30 OF THE CONSTITUTION OF INDIA - Das, Juthika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education is a basic human right which must be accessible to all. An inclusive education is a prerequisite for a just and democratic society. Since its independence, India has given enormous importance to education for all by enacting various acts and policies. However, even after seven decades of independence, a large number of populations particularly the backward sections of society have been deprived of education.Considering the argument, this article attempts to understand the access of education in the context of article 21A and article 30 of the Indian Constitution.